2007
DOI: 10.1002/cncr.22540
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Accuracy of Sentinel Lymph Node Biopsy After Preoperative Chemotherapy in Breast Cancer Patients With Documented Axillary Metastases

Abstract: BACKGROUND.The feasibility and accuracy of sentinel lymph node (SLN) biopsy in patients with breast cancer after preoperative chemotherapy has been demonstrated in a number of large, single‐institution studies. However, a relative contraindication to SLN biopsy after preoperative chemotherapy is the presence of axillary metastases at initial diagnosis. The objective of this study was to determine the feasibility and accuracy of SLN biopsy after preoperative chemotherapy in patients with documented axillary met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(80 citation statements)
references
References 42 publications
2
78
0
Order By: Relevance
“…Clinically N1 patients had an SLN identification rate of 91% and an FNR of 9%, versus 97% and 0%, respectively, in N0 patients [80]. In another study, by Shen et al [81], SLNB following PST in patients with cytologically documented node-positive disease at presentation had a good identification rate (93%) but appeared to have a very high FNR (26%). In conclusion, SLNB following neoadjuvant chemotherapy is not an appropriate method for evaluating the axilla in patients with clinically or cytologically positive axillary lymph nodes at presentation.…”
Section: Challenges Of Surgical Approach After Pstmentioning
confidence: 95%
“…Clinically N1 patients had an SLN identification rate of 91% and an FNR of 9%, versus 97% and 0%, respectively, in N0 patients [80]. In another study, by Shen et al [81], SLNB following PST in patients with cytologically documented node-positive disease at presentation had a good identification rate (93%) but appeared to have a very high FNR (26%). In conclusion, SLNB following neoadjuvant chemotherapy is not an appropriate method for evaluating the axilla in patients with clinically or cytologically positive axillary lymph nodes at presentation.…”
Section: Challenges Of Surgical Approach After Pstmentioning
confidence: 95%
“…There was no difference in identification of sentinel lymph node according to age. Studies by Shen et al 7 and Kinoshita et al 8 included average age of 49 and 51.1 years respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The two main parameters to evaluate SLNB feasibility and accuracy in the context of NAC are the rate of successful SLN identification and the rate of false negative SLN. Regarding locally advanced breast cancer patients, these two criteria have been addressed mostly by small, single-institution studies that reported quite variable values ranging from 86.5%, to 98.0% for SIR and from 0% up to 25.0% for FNR [24][25][26][27]. This variability may be due to the limited number of patients evaluated and to their heterogeneity in terms of tumor size (T1-T4) and clinical node status (N0-N2) within and between studies.…”
Section: Slnb Validation In the Context Of Neo-adjuvant Chemo-therapymentioning
confidence: 99%